Using Gamification and Serious Games to Design a New Curriculum - Tinç, Kutay; Karadayı, Meltem Gülçin (IGI Global, 2020)
Using game elements in class to support the participation of students in learning or designing games that can help educators teach certain subjects more efficiently has been a popular topic in recent years. The former is a matter of gamification, which refers to the application of game elements to other activities so that the activity becomes more engaging or interesting. On the other hand, the latter is about designing a serious game, which can be defined as a game with an explicit and carefully thought out educational purpose. In this study, focused on merging the use of gamification and serious games for a specific engineering course, the authors discuss how the curriculum for this course should be designed so that both sides of the spectrum are facilitated. An application of this union is given with a survey showing the reaction of students to the gamified curricula integrated with a serious game.